2017
DOI: 10.17219/dmp/77898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 980 nm diode laser application protocols on the reduction of Enterococcus faecalis intracanal biofilm: An in vitro study

Abstract: Background. Enterococcus faecalis is associated with a great number of refractory endodontic infections. There is a need to investigate antibacterial properties of laser radiation and create a new alternative technique for root canal disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
0
4
1
Order By: Relevance
“…Among various lasers available, diode laser is probably one of the most effective lasers for the disinfection of S. mutans (Moritz et al 1999;Lee 2006). In study by Prażmo et al 2017), a reduction of bacteria colonies was found when diode laser was used alone, which is in disagreement with the present study; the individual effects of diode laser irradiation were observed, but combination of laser with nanoparticles was evaluated with significantly better results obtained. It attributed to the deep penetration effects of laser followed by antimicrobial effects of nanoparticles.…”
Section: Discussioncontrasting
confidence: 97%
“…Among various lasers available, diode laser is probably one of the most effective lasers for the disinfection of S. mutans (Moritz et al 1999;Lee 2006). In study by Prażmo et al 2017), a reduction of bacteria colonies was found when diode laser was used alone, which is in disagreement with the present study; the individual effects of diode laser irradiation were observed, but combination of laser with nanoparticles was evaluated with significantly better results obtained. It attributed to the deep penetration effects of laser followed by antimicrobial effects of nanoparticles.…”
Section: Discussioncontrasting
confidence: 97%
“…Ewa Joana Prazma et al [15] studied the effects of a 380 W-980 nm diode laser on the reduction in the intracanal biofilm of Enterococcus faecalis and concluded that the diode laser had a significant antibacterial effect and approximately showed a decrease in 87.6% in the double radiation group and 52.5% in the single radiation group. eir results are in line with the results of our study, showing that the use of the diode laser can reduce the number of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Diode lasers have little interference with water and hydroxyapatite due to their flexible fibers, which can easily penetrate into curved canals [14]. Examining the effects of a 980 nm diode laser on reducing the biofilm of Enterococcus faecalis bacteria in a canal, Prazmo et al [15] reported that the number of bacteria significantly decreased in this way. Kerstin Bitter in 2017 also compared the antibacterial effects of ozone gas and a 980 nm diode laser with the antibacterial effects of a canal coated with calcium hydroxide and chlorhexidine gel for one week.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent long-term decannulation rates together with no significant deterioration in voice quality was achieved. Prażmo et al [ 32 ] confirmed a positive effect of the repeated 980 nm laser pulsed irradiation (100 Hz) on intracanal Enterococcus faecalis biofilm elimination.…”
Section: Introductionmentioning
confidence: 99%